ERP software vendors are targeting SMEs with SaaS and SOA offerings – Are these technologies beneficial to SMEs in Singapore when considering adopting ERP? - Lee, Pei Yin Karen (2010)
Many articles that I have researched through the Internet have reflected an optimistic outlook into the Enterprise Resource Planning (ERP)software market despite the economic recession from late 2007 to current. The optimistic forecast was fuelled by globalization, midmarket growth and other factors. It is also due to the new Information Technology (IT) concepts that ERP software companies are adopting to entice midmarket enterprises worldwide to buy their services and products.